Chromium recovery from chrome shaving generated in tanning process - Erdem, M (Elsevier Science Bv, 2006)
In this study, the chromium recovery conditions in the form of soluble chromate from chrome shaving (chromium-containing solid waste) by oxidation with air. oxygen and Na2O2 were investigated and basic Cr(HI) sulphate solution using in the tanning was prepared from the chromate obtained. It has been deter-mined that the oxidation agent is the most effective parameter affecting the chromate formation. While maximum oxidation yields in air and oxygen atmosphere at 850 degrees C were found to be 23.02 and 30.41%, respectively, the highest chromium recovery efficiency in the form of chromate (99.45%) occurred in the presence of eight times Na2O2 with respect to stoichiometric amount of chromium. The chromate generated in Na2O2 oxidation process where 99.45% of chromium in the chrome shaving can be recovered was leached with distilled water and pregnant chromate solution was prepared. The chromate ions in this solution were reduced by using Na2SO3 and Cr(111) sulphate solution was obtained. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: chromium; chromium recovery; tanning waste; chrome shaving; leather processing